Propeller Arm Control System Planning for Flying Electric Vehicles - Muhammad Ainul Mafazi; Sugeng Hadi Susilo (Journal of Evrímata: Engineering and Physics, 2025)
This research aims to design and develop a propeller arm control system for a flying electric vehicle. With the increasing need for efficient and environmentally friendly vehicles, this research focuses on control mechanisms that can improve vehicle maneuverability and speed performance. The research methods used include design planning, making motor mounts, and setting up the control system using the FLYSKY FS-i6 remote control and Lithium Iron Phosphate (LiFePo4) batteries. The results of the research show that the designed propeller arm control system can function well, providing a fast and accurate response to commands from the remote control. This research is expected to make a significant contribution to the development of flying electric vehicle technology, as well as opening up opportunities for further research in the field of automotive electronics.